Flexible multifunctional pressure sensors based on Cu-CAT@CNFN and ZnS:Cu/PDMS composite electrode films for visualization and quantification of human motion. (December 2022) - Hou, Ningle; Zhao, Youwei; Yuan, Tian; Li, Ling; Li, Xiaoting; Zhang, Wenming
Graphical abstract: Highlights: A flexible pressure sensor was fabricated by Cu-CAT@CNFNs and ZnS:Cu/PDMS. The flexible pressure multifunctional sensor can visualize and quantify the pressure. Sensor shows high sensitivity (45.40 kPa −1 ) and quick response (0.166 s) to pressure. The sensor has lotus-inspired microstructure by secondary template method topography. Abstract: Flexible multifunctional pressure sensors for human motion monitoring have recently attracted extensive attention. However, the preparation of a multifunctional sensor with wide coverage and high sensitivity to pressure detection remains a considerable challenge. Here, we design a flexible multifunctional pressure sensor consisting of Cu-catechol nanowire coated carbonized nanofiber networks (Cu-CAT@CNFN) sandwiched between two interlocking polydimethylsiloxane doped with ZnS:Cu (ZnS:Cu/PDMS) composite electrode films. Due to the pressure concentration between the interlock micromastoid arrays and the thicker pressure sensitive layer, the pressure sensors demonstrate a high sensitivity of 45.40 kPa −1, pressure detection coverage of 0 to 110 kPa, a response time of 0.166 s, outstanding cyclic stability of 5, 000 cycles and visualization of the pressure. Furthermore, the pressure sensor can be used to detect pulses, wrist and elbow bending, and finger press. The excellent performance of the pressure sensor demonstrates its application potential in the next generation of wearable electronics.